(untitled) (Scientific Journal of Research Studies in Future Human Sciences, 2026)
This research paper delves into the Conference on Security and Cooperation in Europe (CSCE) and the signing of the Helsinki Final Act in 1975. It highlights the impact of these events on both the dynamics of the Cold War and debates surrounding human rights. The Helsinki Final Act, although not a treaty, played a crucial role in improving relations between the Communist bloc and Western nations. It set in motion what is known as the “Helsinki process,” a series of review meetings to ensure that states adhered to human rights and humanitarian principles. The paper examines how leaders such as U.S. Presidents Jimmy Carter and Ronald Reagan and Soviet leader Mikhail Gorbachev strategically used the Helsinki Accords as tools for reform and how this process contributed to the end of the Cold War. It also explores the varied reactions and interpretations of the Accords in Eastern Europe and in Western countries, emphasizing their role in promoting dialogue, diplomacy, and transnational activism, as well as their indirect influence on political change across Eastern Europe. Finally, it uses international relations theories, especially neoliberal institutionalism and constructivism, to critically evaluate the significance of the Helsinki Accords as evidence of the power of engagement and norms, while also engaging realist and materialist critiques and highlighting the continuing relevance of the Helsinki process in contemporary geopolitical discourse.